What motivates participation in HIV cure trials? A call for real-time assessment to improve informed consent - Holly L. Peay; Gail E. Henderson (Elsevier, 2015)
HIV cure research, a diverse set of studies aimed at eradicating or greatly reducing HIV in latent reservoirs, has become a strategic priority for global AIDS research. However, in early-phase HIV cure research there are ethical challenges related to the uncertainty around potential risks and the risk-benefit balance. Similar to clinical trials in other disease areas, these concerns may impact clinical trial participants' comprehension and decision making. Here we suggest attention to the terminology used to describe HIV cure research that may promote therapeutic misconception, and exploration of the decision-making influences and processes of those who accept and decline participation in HIV cure trials. These data will facilitate efforts to improve protocols and informed consent based on an understanding of participant preferences and needs.